Liquidity, Profitability, and Analysis Market Value Added (MVA) as a Tool for Measuring Financial Performance in Registered Airline Sub-Industry Companies on The Indonesian Stock Exchange - Magdalenna, Lena; Suyanto, Suyanto; Septiani, Ana (Economics and Business International Conference Proceeding, 2024)
This research aimed at analyzing financial performance as measured through analysis of liquidity, profitability, and Market Value Added (MVA) in airline sub-industry companies listed on the Indonesian Stock Exchange. The type of research applied in this research is qualitative with a descriptive approach. The data used in this research is secondary data where the data collection technique uses the documentation method. The data used in this research is in the form of annual financial reports in the form of balance sheets and profit and loss reports for airline sub-industry companies for the 2020-2022 period obtained via the website www.idx.co.id. The sampling technique in this research used purposive sampling technique by several criteria to obtain 3 airline sub-industry companies. The results of this research showed that based on the analysis the liquidity of airline sub-industry companies for the 2020-2022 period is not good. Based on the results of the profitability analysis of airline sub-industry companies for the 2020-2022 period, it is negative. Then, for MVA analysis, there is 1 company that has a positive value, namely the company with the stock code CMPP.